CHRONIC MYELOID LEUKEMIA IN PREGNANCY - Rosa Dwi Wahyuni; Agus Alim Abdullah; Mansyur Arif (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Chronic Myeloid Leukemia (CML) is one of leukemias characterized by abnormal growth of myeloid cells in bone marrow. The Philadelphia chromosome is diagnostic parameter for CML. This chromosome is t(9;22) (q32;q21), a translocation chromosome 9 and 22 relocates a portion of proto-oncogene c-ABL from chromosome 9 to BCR on chromosome 22. Chronic myeloid leukemia consisting of three phases; Chronic, Accelerating and the Blast crisis phase. The clinicaling symptoms of CML are hypercatabolism, splenomegaly, anemia, bruising and sign of Gout. Chronic myeloid leukemia in pregnancy shows a better prognosis than acute leukemia in pregnancy. Chronic myeloid leukemia has the risk of leukocytosis which can lead to uteroplacental insufficiency giving rise to various consequences: fetal growth retardation and perinatal mortality. Moreover, the therapy of CML should be carefully administered considering the fetal effects.  Both sexes have the same risk, mostly in the range of 40 to 60 years old. In this case report, a 38-year-old pregnant female (G1P0A0) with 37 weeks of gestational age was diagnosed as CML on August 2013 and was treated with 500 mg of Cytodrox/Hydroxyurea twice to three times a day until January 2014. Laboratory evaluation on November 10th, 2014, showed leucocytes 449500/µL, erythrocytes 2.58.106/µL, hemoglobin 8.0 g/dL, thrombocytes 437,000/µL and hematocrit 23%. The peripheral blood smear showed normocytic normochromic erythrocytes, anisocytosis, ovalocytes, significantly increased leucocyte count, predominance polymorphonuclear series, all maturation series of myelocytes, 7% myeloblast, normal thrombocyte count and morphology. Based on these evaluations, the patient was diagnosed as CML. The evaluation of Neutrophil Alkaline Phosphatase (NAP) scored 1.